Implementasi Pendidikan Akhlak di SMA Negeri 6 Pariaman - Arman, Agum; Putra, Rido (YASIN, 2025)
Moral education plays a strategic role in shaping students' character; however, SMA Negeri 6 Pariaman still faces moral crises such as bullying and a lack of empathy among students. This phenomenon reflects an educational orientation that prioritizes cognitive and physical aspects, while character development receives less proportional attention. This study aims to examine the planning, implementation, and evaluation of moral education at SMA Negeri 6 Pariaman, as well as to identify its supporting and inhibiting factors. A descriptive qualitative method was employed, with data collected through participatory observation, structured interviews with the principal, vice principal, guidance and counseling teachers, and Islamic Education (PAI) teachers, as well as document analysis. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing, with validation ensured through triangulation of sources, techniques, and time. The findings show that moral education planning is carried out through integration into PAI subjects, extracurricular activities (such as tahfidz), and special programs such as Pesantren Ramadhan, religious seminars, and wirid remaja. Its implementation includes classroom instruction, habituation of positive behavior (6S, cleanliness, discipline), teacher role modeling, and reinforcement through special programs. Evaluation is conducted through daily, mid-semester, and end-of-semester assessments, as well as evaluations of extracurricular activities, all of which show positive contributions to students’ moral development. These findings indicate that the implementation of moral education at SMA Negeri 6 Pariaman is carried out comprehensively through structured and continuous approaches. The study highlights the importance of strengthening student character development strategies and enhancing collaboration among schools, teachers, students, and parents in nurturing morally upright individuals.